Population pharmacokinetic modeling of tribendimidine metabolites in Opisthorchis viverrini-infected adults - Vanobberghen, F; Penny, M; Duthaler, U; Odermatt, P; Sayasone, S; Keiser, J; Tarning, J (American Society for Microbiology, 2016)
There is pressing need for alternative treatments against the liver fluke Opisthorchis viverrini Oral tribendimidine is a promising candidate, but its population pharmacokinetic properties are unknown.Two phase IIa trials were conducted in Laos in O. viverrini-infected adults receiving single oral doses of 25-600 mg tribendimidine, administered as different formulations in each study (study 1 used 200 mg tablets; study 2 used 50 mg tablets). Venous whole-blood, plasma and capillary dried blood spots were sampled frequently from 68 adults and concentrations of tribendimidine metabolites dADT (deacetylated amidantel) and adADT (acetylated dADT) were measured. Population pharmacokinetics were assessed using nonlinear mixed-effects modeling. The relationship between drug exposure and cure (assessed 21 days post-treatment) was evaluated using univariable logistic regression.A six-transit compartment absorption model with a one-disposition compartment for each metabolite described the data well. Compared to the 50 mg formulation (study 2), the 200 mg formulation (study 1) had 40.1% higher mean transit absorption time, 113% higher dADT volume of distribution, and 364% higher adADT volume of distribution. Each ten year increase in age was associated with 12.7% lower dADT clearance and 21.2% lower adADT clearance. Highest cure rates (≥55%) were observed with doses ≥100 mg. Higher dADT, but not adADT, peak concentrations and exposures were associated with cure (p=0.004 and 0.003, respectively).For the first time population pharmacokinetics of tribendimidine has been described. Known differences in the 200 mg versus 50 mg formulations were captured by covariate modeling. Further studies are needed to validate the structural model and confirm covariate relationships.